Analisis Pengaruh Variasi Frekuensi dan Jenis Mesin Produksi Terhadap Output Energi pada Vibrato Harvesting Energy System - Angga Dwi Sapruto (CV. SINAR HOWUHOWU, 2026)
The rapid development of industrial technology has led to a significant increase in electrical energy demand. Meanwhile, mechanical energy in the form of vibrations generated by production machines is largely wasted and has not been optimally utilized. These vibrations have the potential to be converted into electrical energy through piezoelectric-based vibration energy harvesting technology. This study aims to analyze the influence of vibration characteristics and frequency variations of production machines on the electrical energy output generated by an energy harvesting system. The research objects include three types of production machines: pond machines, injection molding machines, and drilling machines, each of which exhibits different vibration characteristics. A quantitative method with an experimental approach was employed in this study. The energy harvesting system was designed using 35 mm diameter PZT piezoelectric elements connected in series. Vibration characteristics were measured using an accelerometer sensor, while voltage and current measurements were carried out using INA219 and ACS712 sensors. Data were collected for 120 seconds for each machine with three repeated tests to obtain accurate and representative results. The experimental data were analyzed using electrical power equations and presented in tables and graphs. The results show that the pond machine produced the highest electrical energy output, with an average voltage of 7.14 V, current of 4.13 mA, and power of 30.66 mW. The injection molding machine generated an average voltage of 4.75 V, current of 2.75 mA, and power of 13.18 mW. Meanwhile, the drilling machine produced the lowest output, with a voltage of 2.45 V, current of 1.41 mA, and power of 3.47 mW. These findings indicate that greater and more stable vibration characteristics result in higher electrical energy output from the vibration energy harvesting system.